Reannotation of the Corynebacterium diphtheriae NCTC13129 genome as a new approach to studying gene targets connected to virulence and pathogenicity in diphtheria - FERREIRA, Vívian D'Afonseca da Silva (Dove Medical Press, 2023)
Background: The reannotation of genomes already on file is a new approach to discovering new genetic elements and to make the genomes more descriptive and current with relevant features regarding the organism’s lifestyle. Within this approach, the present study aimed to reannotate the genome of the Gram-positive human pathogen Corynebacterium diphtheriae, which causes diphtheria. The deposit of massive amounts of information linked to other spe cies of the genus Corynebacterium has facilitated the updating of the genomic interpretation of this microorganism. Additionally, the emergence of invasive disease by nontoxigenic strains of C. diphtheriae and the reemergence of diphtheria in partially immunized populations have given impetus to new studies in relation to its structural and functional genome. Results: In relation to structural genomics, 23 coding regions (coding sequences) were deleted and 71 new genes were added to the genome annotation. Nevertheless, all the pseudogenes were validated and ten new pseudogenes were created. In relation to functional genomics, about 57% of the genome annotation was updated and became functionally more informative. The product descriptions of 41% (973 proteins) were updated. Among them, 370 that were previously annotated as “hypothetical proteins,” now have more informative descriptions. With the new annotation, the plasticity of the genome became evident, which shows improvements in the annotation of 13 pathogenicity islands already described in the literature. In addition, the large number of transposases and the presence of structural genes of bacteriophages make their genomic versatility evident. Contrasting with this reality, it also allowed the clarification of some aspects concerned with mechanisms used by C. diphtheriae to stop the invasion of the genome by bacteriophages, mediated by the clustered regularly interspaced short palindromic repeats region. Conclusion: The reannotation of the C. diphtheriae genome provided an improvement in annotation of the C. diphtheriae genome in several aspects, such as virulence characteristics and plasticity events. Moreover, the protocol used here can be extended to various other pathogens in order to improve the genomic information already on file in public databases and to minimize propagating errors. The reannotated archive and updated archive are available at: http://lgcm. icb.ufmg.br/pub/C_diphtheriae_reannotation.embl.